Challenges Faced by Young Mothers with a Care History and Views of Stakeholders About the Potential for Group Family Nurse Partnership to Support Their Needs. (5th July 2017) - Datta, Jessica; Macdonald, Geraldine; Barlow, Jane; Barnes, Jacqueline; Elbourne, Diana
Abstract : Women with experience of being 'looked after' are more likely than their peers to become young mothers. There has been limited research investigating support for their needs. This study, embedded in a randomised trial of Group Family Nurse Partnership (gFNP), involved interviews with young mothers with care experience, Family Nurses delivering group gFNP, and health and social care professionals. This first qualitative study to explore the views of these varied stakeholders found consensus regarding young mothers' social isolation and lack of trusting relationships but diversity in views about the potential of gFNP to meet their needs.